2016
DOI: 10.1007/s00464-016-4957-z
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of clinical outcome of laparoscopic versus open appendectomy for complicated appendicitis

Abstract: The laparoscopic approach for complicated appendicitis is a safe and feasible procedure. Surgeons should be aware of a potentially higher incidence of intraabdominal abscess formation following LA. Use of endobags , inversion of the appendiceal stump and carefully conducted local irrigation of the abdomen in a supine position may reduce the incidence of abscess formation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
66
3
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 77 publications
(77 citation statements)
references
References 29 publications
6
66
3
2
Order By: Relevance
“…In this study, we found female preponderance and younger age. This finding is consistent with other studies [2,3,5]. As for other reported studies this study findings are consistent with the past experience in other population with regards to post-operative outcomes [8,10,11,13].…”
Section: Discussionsupporting
confidence: 94%
See 4 more Smart Citations
“…In this study, we found female preponderance and younger age. This finding is consistent with other studies [2,3,5]. As for other reported studies this study findings are consistent with the past experience in other population with regards to post-operative outcomes [8,10,11,13].…”
Section: Discussionsupporting
confidence: 94%
“…Most studies opined in favor of LA [1][2][3]4,5,7]. In this study, we found female preponderance and younger age.…”
Section: Discussionsupporting
confidence: 65%
See 3 more Smart Citations